A U-shaped association between the triglyceride to high-density lipoprotein cholesterol ratio and the risk of incident type 2 diabetes mellitus in Japanese men with normal glycemic levels: a population-based longitudinal cohort study - Song, Bei; Wang, Kun; Lu, Weilin; Zhao, Xiaofang; Yao, Tianci; Liu, Ting; Gao, Guangyu; Fan, Haohui; Liu, Chengyun (Frontiers in Endocrinology, 2023)
Background: A number of studies have verified that high baseline TG/HDL-C was a risk factor for incident type 2 diabetes mellitus (T2DM). However, for low baseline TG/HDL-C, the findings were not consistent with ours. In addition, the association between baseline TG/HDL-C and the risk of incident T2DM in Japanese men with normal glycemic levels was unclear. As a result, our study further investigated the relation between baseline TG/HDL-C and the risk of incident T2DM in Japanese men with normal glycemic levels.Methods: Our study was a longitudinal cohort secondary study. We selected 7,684 male participants from NAGALA database between 2004 and 2015. Standardized Cox regression model and two-piecewise Cox regression models were used to explore the relationship between baseline highdensity lipoprotein cholesterol ratio (TG/HDL-C) and incident T2DM.Results: During a median follow-up of 2282 days, 162 men developed incident T2DM. In the adjusted model, the baseline TG/HDL-C was strongly associated with the risk of incident T2DM, and no dose-dependent positive association was observed between the baseline TG/HDL-C and the incidence of T2DM throughout the baseline TG/HDL-C quartiles. Two-piecewise linear regression analysis showed a U-shaped association between baseline TG/HDL-C and the incidence of incident T2DM. Baseline TG/HDL-C below 1.188 was negatively associated with incident T2DM (H.R. = 0.105, 95% CI= 0.025, 0.451; P=0.002). In contrast, baseline TG/HDL-C higher than 1.188 was positively associated with incident T2DM (H.R. = 1.248, 95% CI=1.113, 1.399; P<0.001). The best threshold of TG/HDL-C for predicting incident T2DM was 1.8115 (area under the curve 0.6837).